2019
DOI: 10.1038/s41598-019-51278-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the PEBP Family Genes in Moso Bamboo (Phyllostachys heterocycla)

Abstract: Moso bamboo is one of the economically most important plants in China. Moso bamboo is a monocarpic perennial that exhibits poor and slow germination. Thus, the flowering often causes destruction of moso bamboo forestry. However, how control of flowering and seed germination are regulated in moso bamboo is largely unclear. In this study, we identified 5 members (PhFT1-5) of the phosphatidyl ethanolamine-binding proteins (PEBP) family from moso bamboo genome that regulate flowering, flower architecture and germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 81 publications
(105 reference statements)
2
12
0
Order By: Relevance
“…In the present study, four TFL1 genes were obtained from 'SiJiMi' mango, and these were named MiTFL1-1, MiTFL1-2, MiTFL1-3 and MiTFL1-4. Multiple copies of TFL1 homologous genes were also found in other plants, such as two in soybean [29], moso bamboo [13] and loquat [30], three in petunia [31], four in cotton [32] and ve in Hevea brasiliensis [33]. In a previous study, only two TFL1 genes, MiTFL1 and MiTFL1a, were found in another mango variety, 'Alphonso', and these corresponded to MiTFL1-2 and MiTFL1-1 in the present study, respectively [34].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the present study, four TFL1 genes were obtained from 'SiJiMi' mango, and these were named MiTFL1-1, MiTFL1-2, MiTFL1-3 and MiTFL1-4. Multiple copies of TFL1 homologous genes were also found in other plants, such as two in soybean [29], moso bamboo [13] and loquat [30], three in petunia [31], four in cotton [32] and ve in Hevea brasiliensis [33]. In a previous study, only two TFL1 genes, MiTFL1 and MiTFL1a, were found in another mango variety, 'Alphonso', and these corresponded to MiTFL1-2 and MiTFL1-1 in the present study, respectively [34].…”
Section: Discussionmentioning
confidence: 85%
“…TFL1 encodes proteins with conserved His88 and Asp144 residues and the typical amino acid triad modules EYD, YFG, and END [12]. The FT protein does not have this structure, which is an important reason for the opposite functions of these two genes [13]. TFL1 genes, as owering repressors, determine the timing of the transition of the apical meristem into an in orescence meristem and the branching pattern of the in orescence [14].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies on the regulatory pathways of flowering behavior in moso bamboo revealed that genes such as PheDof1 , PheMADS14 , and six microRNAs were critical in these pathways (Ge et al., 2017). Further, molecular mechanisms governing moso bamboo flowering and growth control have very recently been elucidated (Yang, Chen, et al, 2019; Zhang, Tang, et al, 2018). Furthermore, Liu, Cheng, Xie, Li, and Gao (2019) observed that PheDof was highly expressed in bamboo leaves during flowering, the activity of which declines during flower development.…”
Section: Development Of Genomic Resources For Identifying Genes Undermentioning
confidence: 99%
“…Bamboos are key members of the Gramineae plants and have approximately 90 genera and 1200 species [1,2]. The bamboo output is a key source of non-wood forest products, and bamboo plantations and forests have been continuously increasing in tropical, subtropical and temperate regions [1,2]. After industrial treatment, bamboos have up to 95% glucose and 73% ethanol yield [3].…”
Section: Introductionmentioning
confidence: 99%